Bibliometric Analysis of Renewable Natural Gas (Biomethane) and Overview of Application in Brazil - Machado, Mônica Valéria dos Santos [UNESP]; Ávila, Ivonete [UNESP]; de Carvalho, João Andrade [UNESP] (MDPI, 2024)
In view of the increasing demand for clean energy and the growing awareness of environmental sustainability, a bibliometric study examines the various facets of renewable natural gas (biomethane). Sustainable fuels are gaining importance as an alternative to fossil fuels because they are renewable and can reduce greenhouse gas emissions. In addition, an overview of the use of biomethane was compiled for Brazil. The country was chosen because it is the authors’ home country. These emerging energy sources have the potential to play a critical role in the transition to a cleaner, more sustainable and cost-effective energy landscape, thereby reducing environmental impact and strengthening the resilience of our energy future.
Keywords: biomethane; renewable energy sources; renewable natural gas